Improving the performance of photovoltaic panels by cooling them with water - اسكندر ميرال; رامـي جـورج; مسعود صبيح (Latakia University Journal -Engineering Sciences Series, 2024)
Syria is blessed with plenty of sunshine over the whole year. The solar photovoltaic system is an appropriate alternative for the production of electricity. One of the major problems of photovoltaic plates PV is high temperature due to excessive solar radiation and high ambient temperature leads to reduced efficiency in solar panels. The hybrid photovoltaic thermal (PV/T) systems are one of the most common methods for cooling photoelectric panels and improve performance. The (PV/T) systems are an solar technology that the enables simultaneous the conversion of solar energy into electrical and thermal energy. The heat from the PV panel is transferred through working fluids such as water. The extracted heat is used in low temperature applications, including household hot water This paper discusses indoor experimental studies of the water-based (PV/T) system and compares this system with a normal PV panel without a cooling system. The (PV/T) system combined with solar water heater. The results of the tests showed that the value of the current and voltage of the panel (PV/T) increased compared to the reference pane (PV). As well as a decrease in the temperature of the back surface of the panel (PV/T) compared to the reference panel (PV), where the value of the decrease reached from8 [°C] to 12 [°C], and increase in the temperature of the water coming out of the solar water heater, where the value of the increase reached from 6[°C] to 10 [°C].